2017
DOI: 10.1111/all.13161
|View full text |Cite
|
Sign up to set email alerts
|

New approach shows no association between maternal milk fatty acid composition and childhood wheeze or asthma

Abstract: Using appropriate statistical methodology, we report null associations. These findings may partly be attributable to several cohort-specific factors associated with breastfeeding and breastmilk collection. Further studies could improve on ours by analyzing samples of breastmilk and formula and by including all children for whom these are exclusively or together the major source of fatty acids in the first months of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 27 publications
0
31
2
Order By: Relevance
“…We suspected that GM feeding during pregnancy and lactation might change the composition of breast milk and confer immunological maturation and colonization of gut microbiota on offspring, and this might suppress atopy development and downregulate airway inflammation. Relationships among a wide spectrum of bioactive factors, such as proteins, polyunsaturated fatty acids, oligosaccharides, microbial content, metabolites, and micronutrients present in breast milk and allergy development in infants have attracted more attention (36)(37)(38)(39). Various maternal exposures during pregnancy, such as immunization, dietary patterns, vitamin D, omega-3 fatty acids, and/or probiotics may affect breast milk composition and thereby influence the early colonization of gut microbiota and infant health (16,40).…”
Section: Discussionmentioning
confidence: 99%
“…We suspected that GM feeding during pregnancy and lactation might change the composition of breast milk and confer immunological maturation and colonization of gut microbiota on offspring, and this might suppress atopy development and downregulate airway inflammation. Relationships among a wide spectrum of bioactive factors, such as proteins, polyunsaturated fatty acids, oligosaccharides, microbial content, metabolites, and micronutrients present in breast milk and allergy development in infants have attracted more attention (36)(37)(38)(39). Various maternal exposures during pregnancy, such as immunization, dietary patterns, vitamin D, omega-3 fatty acids, and/or probiotics may affect breast milk composition and thereby influence the early colonization of gut microbiota and infant health (16,40).…”
Section: Discussionmentioning
confidence: 99%
“…Clr transformations were applied to fatty acid data to account for compositionality. Clr was calculated as the natural log of the quotient of the individual fatty acid concentration over the geometric mean of all fatty acid concentrations within a sample [22]. The geometric mean was used as the denominator as it is a meaningful measure of central tendency for variables with skewed distributions.…”
Section: Discussionmentioning
confidence: 99%
“…10,[28][29][30] In addition to m-sCD14, several other breast milk components have been implicated as possible targets for further research including transforming growth factor (TGF)-β, 23,31 interleukin (IL)-10, 31 erythropoietin, lactoferrin, certain fatty acids and inflammation-related hormones such as leptin. 8,29,32 Finally, some have suggested that breastfeeding may differentially affect AD outcomes among children with genetic predisposition to skin barrier dysfunction. 33 Therefore, gene loci associated with atopy or specifically atopic dermatitis may also serve as additional targets for study.…”
Section: Discussionmentioning
confidence: 99%